Going beyond the 2023 MASCC and ESMO guideline update for the prevention of chemotherapy- and radiotherapy-induced nausea and vomiting - Jordan, Karin; de Azambuja, Evandro; Del Barrio, María Ángeles García; Jahn, Franziska; Di Palma, Mario; Scotté, Florian; Molassiotis, Alex; Aapro, Matti S. (European journal of cancer, 2025)
The MASCC/ESMO guidelines for the prevention of chemotherapy- and radiotherapy-induced nausea and vomiting were updated in 2023 by a Consensus Committee of 34 multidisciplinary international healthcare professionals and three patient advocates. Guideline-recommended prophylactic anti-emetic strategies can control chemotherapy-induced nausea and vomiting (CINV) in many patients, but unaddressed issues remain. Across a series of meetings, we evaluated these guidelines to identify possible evidence gaps which warrant further exploration. Key topics identified and discussed included the use of dexamethasone-sparing regimens with cisplatin (and other non-anthracycline and cyclophosphamide)-based highly emetogenic chemotherapy regimens, the importance of individual patient risk factors for CINV, the use of a second agent in patients receiving low emetogenic chemotherapy, how to manage CINV with certain new antibody-drug conjugates, the most appropriate approach for managing breakthrough CINV, the options for patients with CINV even after following best guidance, the use of lower than standard doses of olanzapine (<10 mg/day), and the management of long-delayed CINV and CINV in patients receiving oral therapies. Through identifying the current gaps in the updated MASCC/ESMO guidelines and discussing the available evidence, we aim to address these issues and support oncologists who may encounter them in clinical practice. These and other questions need to be considered to help ensure choice of anti-emetic treatments provide optimal effectiveness in clinical practice.
Gesehen am 05.11.2025